Robby Müller : cinematography - Deursen, Linda van; Vries, Marietta; Wenders, Wim (Zurich : JRP/Ringier, 2013)
Robby Müller is one of the most inspiring cinematographers of our time. His influence is noticeable in his long-term collaborations with directors such as Wim Wenders and Jim Jarmusch and his groundbreaking work for films as 'Breaking the Waves' and 'Dancer in the Dark' by Lars von Trier. He not only helped to shape their films, but his contribution also reveals an adventurous and creative vision which can also be seen in other films by directors such as Alex Cox and Barbet Schroeder. This publication gives a visual insight in his artistic flexibility and technical expertise as a cinematographer, and reveals his passionate pleasure in the nature of light in all its manifestations.
boek
Keywords: Müller, Robby